Signifikansi Peran Eksekutif, Legislatif, dan Yudikatif bagi Eksistensi Sistem Single Bar demi Tegaknya Negara Hukum (Significance of the Role of the Executive, Legislative, and Judiciary for the Existence of a Single Bar System to Uphold the Rule of Law) - Ramsen Marpaung (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2022)
The split of the advocates’ organizations in Indonesia has damaged the existence of a single bar system for upholding the rule of law because a weak single bar system can no longer guarantee the quality of advocates who could always uphold the principles of the rule of law. To overcome this, the executive, legislative, and judiciary roles must be optimized so that the policies and decisions regarding this issue would not further divide advocates’ organizations. This article examines the significance of the executive, legislative, and judiciary roles in maintaining the existence of a single bar system to uphold the supremacy of law, equality before the law, and human rights. The writing method used is normative juridical with approaches to laws, cases, comparisons, history, and concepts through library studies for secondary data, then analyzed descriptively and qualitatively. As for the discussion, it is known that the single bar system has been tested for its existence throughout the world. Only a single bar system can realize the advocates’ ideals to counsel quality advocates, which means at the same time guaranteeing fair law enforcement. For this reason, and for the achievement of national development goals especially in the field of law, a comprehensive and coordinated role of the executive, legislative, and judiciary is needed to resolve the split of the advocates’ organizations by returning and strengthening the Indonesian advocates’ organizations to a single bar system based on the Law on Advocates.AbstrakKondisi perpecahan organisasi advokat di Indonesia telah merusak eksistensi sistem single bar terhadap tegaknya rule of law karena bangunan sistem single bar yang lemah tidak dapat lagi menjamin kualitas advokat yang selalu mampu menegakkan prinsip-prinsip negara hukum. Untuk mengatasinya peran eksekutif, legislatif, dan yudikatif harus lebih dioptimalkan sehingga kebijakan dan keputusan yang ditetapkan tidak lagi berdampak semakin memperuncing perpecahan organisasi advokat. Artikel ini mengkaji signifikansi peran eksekutif, legislatif, dan yudikatif dalam menjaga eksistensi sistem single bar demi tegaknya supremacy of law, equality before the law, human rights. Metode penulisan yang digunakan adalah yuridis normatif dengan endekatan undangundang, kasus, perbandingan, sejarah, dan konsep melalui studi perpustakaan untuk menemukan data sekunder yang dianalisis secara deskriptif kualitatif. Adapun dari pembahasan diketahui bahwa sistem single bar telah teruji eksistensinya di seluruh dunia. Hanya sistem single bar yang dapat mewujudkan cita-cita advokat untuk membentuk advokat yang berkualitas, yang berarti sekaligus menjamin penegakan hukum yang berkeadilan. Untuk itu, demi terealisasinya tujuan pembangunan nasional, khususnya bidang hukum, maka peran eksekutif, legislatif, dan yudikatif secara komprehensif dan terkoordinasi sangat diperlukan dalam upaya menyelesaikan perpecahan organisasi advokat dengan mengembalikan dan memantapkan organisasi advokat Indonesia ke sistem single bar sesuai dengan Undang-Undang Advokat.